Distal and proximal colon cancers differ in terms of molecular, pathological, and clinical features - Missiaglia, E; Jacobs, B; D'Ario, G; Di Narzo, A F; Soneson, C; Budinska, E; Popovici, V; Vecchione, L; Gerster, S; Yan, P; Roth, A D; Klingbiel, D; et al. (Annals of oncology, 2014)
BACKGROUND: Differences exist between the proximal and distal colon in terms of developmental origin, exposure to patterning genes, environmental mutagens, and gut flora. Little is known on how these differences may affect mechanisms of tumorigenesis, side-specific therapy response or prognosis. We explored systematic differences in pathway activation and their clinical implications. MATERIALS AND METHODS: Detailed clinicopathological data for 3045 colon carcinoma patients enrolled in the PETACC3 adjuvant chemotherapy trial were available for analysis. A subset of 1404 samples had molecular data, including gene expression and DNA copy number profiles for 589 and 199 samples, respectively. In addition, 413 colon adenocarcinoma from TCGA collection were also analyzed. Tumor side-effect on anti-epidermal growth factor receptor (EGFR) therapy was assessed in a cohort of 325 metastatic patients. Outcome variables considered were relapse-free survival and survival after relapse (SAR). RESULTS: Proximal carcinomas were more often mucinous, microsatellite instable (MSI)-high, mutated in key tumorigenic pathways, expressed a B-Raf proto-oncogene, serine/threonine kinase (BRAF)-like and a serrated pathway signature, regardless of histological type. Distal carcinomas were more often chromosome instable and EGFR or human epidermal growth factor receptor 2 (HER2) amplified, and more frequently overexpressed epiregulin. While risk of relapse was not different per side, SAR was much poorer for proximal than for distal stage III carcinomas in a multivariable model including BRAF mutation status [N = 285; HR 1.95, 95% CI (1.6-2.4), P < 0.001]. Only patients with metastases from a distal carcinoma responded to anti-EGFR therapy, in line with the predictions of our pathway enrichment analysis. CONCLUSIONS: Colorectal carcinoma side is associated with differences in key molecular features, some immediately druggable, with important prognostic effects which are maintained in metastatic lesions. Although within side significant molecular heterogeneity remains, our findings justify stratification of patients by side for retrospective and prospective analyses of drug efficacy and prognosis.
Keywords: mutations; regulace genové exprese u nádorů; mikrosatelitní nestabilita; nádorové proteiny; Humans; nádory tračníku; Microsatellite Instability; Colonic Neoplasms; Female; oncogenic pathways; expression profiling; DNA Copy Number Variations; lidé; přežití bez známek nemoci; colon cancer; survival; Translational Research, Biomedical; Neoplasm Metastasis; metastázy nádorů; staging nádorů; ženské pohlaví; Male; prognóza; Proto-Oncogene Mas; variabilita počtu kopií segmentů DNA; Disease-Free Survival; Neoplasm Staging; lokální recidiva nádoru; Neoplasm Proteins; mužské pohlaví; protoonkogen Mas; translační biomedicínský výzkum; Gene Expression Regulation, Neoplastic; Neoplasm Recurrence, Local; Prognosis